Perkembangan Politik dan Dinamika Kelembagaan di Indonesia dan Filipina: Analisis Politik Komparatif - Muhammad Pasha Fathurilham (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes the political development and institutional dynamics of Indonesia and the Philippines through a comparative politics approach. The research focuses on six main aspects, namely historical background, political system, governmental system, party system, socio-cultural characteristics, and socio-economic conditions. The study employs a qualitative comparative method based on literature review using academic books, journal articles, and reports from international institutions. The analytical framework is grounded in the theories of political development by Huntington (1968), comparative politics by Almond and Powell (1966), political culture by Almond (1960), and institutionalism by North (1990). The findings indicate that Indonesia and the Philippines share several similarities as democratic presidential states in Southeast Asia that experienced colonialism and democratic transition. However, significant differences exist in political institutionalization, party system development, governance effectiveness, and political culture. Indonesia demonstrates stronger democratic consolidation and party institutionalization following the Reformasi era, while the Philippines continues to experience the dominance of political dynasties and patron-client relations. In socio-economic terms, both countries have achieved steady economic growth, yet challenges such as inequality, poverty, and governance quality remain evident. The study concludes that institutional capacity, political culture, and governance effectiveness are decisive